Hubungan Dukungan Keluarga Terhadap Penerimaan Diri dan Motivasi Menjalani Kemoterapi pada Pasien Ca Mammae di RSI Sultan Agung Semarang - Naila Hilya; Ahmad Ikhlasul Amal; Erna Melastuti (STIKes Ibnu Sina Ajibarang, 2025)
Based on statistical data, Ca Mammae is the most prevalent cancer type found in the female population in Central Java. Patients undergoing chemotherapy are at risk of experiencing psychological stress, which can impact their self-acceptance and motivation to continue their treatment. The purpose of this study is to examine the correlation between family support and its impact on self-acceptance levels and motivation to undergo chemotherapy in breast cancer patients at RSI Sultan Agung Semarang. This research uses a non-experimental, quantitative design with a cross-sectional approach. Data collection occurred from October to December 2024 at the Ma'wa room of RSI Sultan Agung Semarang, with a sample of 77 respondents selected through purposive sampling. The statistical analysis employed the Somer's method. The results showed that the average age of the respondents was 49 years, all were female, and most were married. On average, the participants were in their sixth chemotherapy cycle and had been diagnosed with breast cancer for approximately 25 months. The majority of respondents had good family support, high self-acceptance, and strong motivation to undergo chemotherapy. The data analysis revealed a significant correlation between family support and self-acceptance in chemotherapy patients, with a p-value of 0.021 (< 0.05), as well as a significant relationship between family support and chemotherapy motivation, with a p-value of 0.003 (< 0.05).